Front Cover: Stepwise Assembly of an Electroactive Framework from a Co6S8 Superatomic Metalloligand and Cuprous Iodide Building Units (Chem. Eur. J. 55/2020). Issue 55 (1st September 2020) - Freeman, Matthew B.; Edokobi, Ozioma D.; Gillen, Jonathan H.; Kocherga, Margaret; Dipple, Kathleen M.; Jones, Daniel S.; Paley, Daniel W.; Wang, Le; Bejger, Christopher M.
Abstract : A double‐cluster framework comprising octahedral Co6 S8 superatoms, tetrahedral Cu4 I4 clusters, and 1, 3, 5‐triaza‐7‐phosphaadamantane (PTA) bifunctional linkers was prepared using a stepwise approach. The synthesis relies on the use of a stable, pre‐formed Co6 S8 (PTA)6 superatomic‐metalloligand, which can undergo further coordination‐driven assembly in the presence of CuI. The resulting three‐dimensional coordination polymer exhibits reversible redox behavior in the solid state. The artwork portrays a pair of star clusters known as the Double Cluster, which resides in the northern part of the constellation Perseus. The star clusters are 7500 light years from Earth and each contain 300 to 400 stars that can be viewed using a pair of binoculars. Illustration by Frank A. Martinez. More information can be found in the Communication by L. Wang, C. M. Bejger, et al. on page 12523 .